Evaluating the Economic and Social Impact of the Construction of the Border Market and Its Role in the Development of Urban Areas (Case Study: Market of Hendijan City) - Zahre Moradi; Maryam Ilanloo (تحقیقات کاربردی علوم جغرافیایی)
The border regions (periphery) are far away from the center due to remoteness, geographical isolation, lack of development, and ... great differences in terms of prosperity and development with central centers. Creating and operating a border market can modify the one-way central- Around and improve regional prosperity. The purpose of this study was to investigate the role of the border market in Henijan province in Khuzestan province in the socio-economic development of the region. The population of the population is Hendijan city which consists of 26292 people according to the census of 2011. Using Cochran formula, 380 people were selected and the questionnaire was distributed among them. The questionnaire has five components: economic, social, transportation, urban services and infrastructure, and 27 sub-criteria. For data analysis, the Fuzzy Network Analysis (ANP) and inferential statistics of Chi-Square have been used.Based on the fuzzy ANP model, the construction of the bazaar has had the greatest impact in reducing smuggling, increasing the stores and shops, hotel and restaurant construction, attracting tourists, increasing passenger terminals, increasing service occupations, boosting banks and insurers, earning income, employing indigenous people and reducing immigration. had. Based on the results, the market has the most impact on the economic component and the least on the underlying component.  The fuzzy network analysis model indicates that the market has been most effective in improving. the conditions of which of the components and sub-criteria has the most effect in helping users and planners in the region to use the cost to improve other components